Panoptic Vision: Disjuncture, Transgressions, and Imagination in Laila Marrakchi’s Film Rock the Casbah - Touria Khannous (Journal of Global Initiatives, 2019)
This article focuses on Laila Marrakchi’s film Rock the Casbah (2013), which reflects the exchange between global and local cultural and sociopolitical ideologies of a new Morocco. The film highlights the contradictions of globalization as it occurs through disjuncture. Arjun Appadurai’s theory of the world in motion and “a world of flows” provides a relevant framework for this analysis. The article uses Appadurai’s notion of “disjuncture” as a theoretical framework to discuss the dynamics and interrelationships involved in the protagonist’s movement between Western mediascapes as a filmstar and her Moroccan family’s local context. Appadurai’s conceptualization of globalization is crucial for understanding the inherent disjuncture between the homogeneity of media representations and the local heterogeneity of Morocco. One aspect of the film represents the reality of a changing, glocalized Morocco. Another engages with Western media tropes in order to reveal the false representations of reality that are often depicted in Western films. The film’s panoptic vision reveals the power structures present in both the local and global contexts, inspiring the viewer to imagine new identities and to be more aware of glocal possibilities.